The Influence of Product, Price, and Promotion on Consumer Purchase Intention at the Romi Spice Shop, Palembang Central Market - Mario Minaldi; Siti Komariah Hildayanti; Endah Dewi Purnamasari (Journal of Entrepreneurial and Business Diversity, 2026)
Purpose:The development of the trade sector in Indonesia has shown increasingly competitive dynamics, particularly in traditional markets that must adapt to changing consumer behavior. Competition among traders selling similar products requires business actors to understand the factors that influence consumer purchase intention. Toko Bumbu Romi, located in Pasar Induk Palembang, has experienced a decline in the number of customers, making it necessary to examine marketing factors that may influence consumer purchase intention. This study aims to analyze the effect of product, price, and promotion on consumer purchase intention at Toko Bumbu Romi Pasar Induk Palembang.Methodology:This research uses a quantitative approach with data collected through questionnaires distributed to consumers who have shopped at Toko Bumbu Romi. The sample size was determined using the Cochran formula, resulting in 385 respondents. Data were analyzed using multiple linear regression with the assistance of SPSS software through validity tests, reliability tests, classical assumption tests, and hypothesis testing using t-test and F-test.Findings:The results show that partially the variables of product, price, and promotion do not have a significant effect on consumer purchase intention. Furthermore, the simultaneous test also indicates that these three variables together do not significantly influence consumer purchase intention at Toko Bumbu Romi Pasar Induk Palembang.Implication:The findings indicate that the three examined marketing variables do not significantly influence consumer purchase intention at the research location.